Applied transport economics policy, management & decision making - Cole Stuart (London Kogan Page, 2006)
This edition covers the latest developments and thinking in transport economics. Professor Stuart Cole examines the application of economics techniques first to commercial transport operations, and second to public policy issues such as investment, integ
Keywords: Transportation; Transportation and state